Chronic Cadmium Exposure can Alter Energy Allocation to Physiological Functions in the Shrimp Penaeus vannamei - da Costa, Juliana Rodrigues [UNESP]; Capparelli, Mariana V.; Padilha, Pedro Magalhães [UNESP]; Borges, Emanuelle [UNESP]; Ramaglia, Andressa C. [UNESP]; dos Santos, Michelle Roberta [UNESP]; Augusto, Alessandra [UNESP] (Springer Nature, 2024)
Environmental stressors in aquatic organisms can be assessed using a bioenergetic approach based on the evaluation of changes in their physiological parameters. We evaluated the chronic effects of cadmium (Cd2+) on the energy balance as well as the survival, growth, metabolism, nitrogen excretion, hepatosomatic index, oxidized energy substrate, and osmoregulation of the shrimp Penaeus vannamei with the hypothesis that the high energy demand related to the homeostatic regulation of Cd2+could disrupt the energy balance and as a consequence, their physiological functions. The shrimp exposed to Cd2+ had higher mortality (30%), directed more energy into growth (33% of energy intake), ingested 10% more energy, and defecated less than control animals. Cd2+ exposure caused a tendency to decrease metabolism and ammonia excretion but did not alter the hepatosomatic index, type of energy substrate oxidized, and the hyperosmorregulatory pattern of the species. The Cd+2 exposure may have induced a trade-off response because there was a growth rate increase accompanied by increased mortality.